Testing the metabolic homeostasis hypothesis in amphibians - Kreiman, Lucas E. (Philos Trans R Soc Lond B Biol Sci, 2019)
A number of hypotheses about compensatory mechanisms that allow ectothermic animals to cope with the latitudinal decrease in ambient temperature (T(A)) have been proposed during the last century. One of these hypotheses, the ‘metabolic homeostasis’ hypothesis (MHH), states that species should show the highest thermal sensitivity of the metabolic rate (Q(10-SMR)) at the colder end of the range of T(A)s they usually experience in nature. This way, species should be able to minimize maintenance costs during the colder hours of the day, but quickly take advantage of increases in T(A) during the warmer parts of the day. Here, we created a dataset that includes Q(10-SMR) values for 58 amphibian species, assessed at four thermal ranges, to evaluate three predictions derived from the MHH. In line with this hypothesis, we found that: (i) Q(10-SMR) values tended to be positively correlated with latitude when measured at lower T(A)s, but negative correlated with latitude when measured at higher T(A)s, (ii) Q(10-SMR) measured at lower T(A)s were higher in temperate species, whereas Q(10-SMR) measured at higher T(A)s were higher in tropical species, and (iii) the experimental T(A) at which Q(10-SMR) was maximal for each species decreased with latitude. This is the first study to our knowledge showing that the relationship between Q(10-SMR) and latitude in ectotherms changes with the T(A) at which Q(10-SMR) is assessed, as predicted from an adaptive hypothesis. This article is part of the theme issue ‘Physiological diversity, biodiversity patterns and global climate change: testing key hypotheses involving temperature and oxygen’.